Differences in Linear Epitopes of Ara h 9 Recognition in Peanut Allergic and Tolerant, Peach Allergic Patients - Sánchez-Ruano, L.; Fernández-Lozano, C.; Ferrer, M.; Gómez, F.; de la Hoz, B.; Martínez-Botas, J.; Goikoetxea, M. J. (Frontiers in Allergy, 2022)
Background: Mediterranean peanut-allergic patients are mostly sensitized to the lipid transfer protein (LTP) Ara h 9, and the peach LTP Pru p 3 seems to be the primary sensitizer. However, LTP sensitization in peanut allergy is not a predictive marker for clinically relevant symptoms. Objective: We aimed to identify sequential epitopes of IgE and IgG4 from Pru p 3, and Ara h 9 in peach allergic patients sensitized to peanuts. We also sought to determine the differences in IgE and IgG4 binding between patients who had develop peanut allergy and those tolerating peanuts. Methods: Forty-six peach allergic patients sensitized to peanut were selected. Thirty-five patients were allergic to peanut (peanut allergic group) and eleven were tolerant to peanut (peanut tolerant group). We examined the IgE and IgG4 binding to sequential epitopes using a peptide microarray corresponding to lineal sequences of the LTP Ara h 9 and Pru p 3. Results: The frequency and the intensity of IgE recognition of Ara h 9 and Pru p 3 peptides were higher in the peanut-tolerant group than in peanut-allergic group. We found four Ara h 9 peptides (p4, p14, p21, and p25) and four Pru p 3 peptides (p1, p3, p21, and p24) with a significantly elevated IgE recognition in peanut tolerant patients. Interestingly, only one peptide of Ara h 9 (p4) recognized by IgG4 was significantly elevated in the peanut-tolerant group. The IgG4/IgE ratio of Ara h 9 peptide 4 was significantly higher in peanut tolerant patients than in peanut allergic patients, while no significant differences were observed in the IgG4/IgE ratio of this peptide in Pru p 3. Conclusion: Although we found significant differences in IgE and IgG4 of Ara h 9 and also Pru p 3 between peanut tolerant and peanut allergic patients being all of them allergic to peach, polyclonal IgE peptide recognition to both LTPs was observed in peach allergic patients tolerating peanuts. However, the blocking IgG4 antibodies against Ara h 9 peptide 4 could provide an explanation for the absence of clinical reactivity in peanut tolerant peach allergic patients and arises as promising tolerance predictive biomarker.